The use of administrative sanctions to prevent environmental damage in impact assessment follow-ups. (1st August 2018) - Garcia, Luiz Carlos; Fonseca, Alberto
Abstract: Scholars have long been highlighting the value of administrative sanctions in improving environmental policy enforcement. However, few studies have evaluated how such sanctions are implemented, particularly in the context of environmental impact assessments (EIA) and their respective follow-up programs. The main objective of this article was to evaluate how administrative sanctions have been used in EIA follow-ups, using the Brazilian state of Minas Gerais as the empirical context. More specifically it tried to understand what have been the main triggers, frequency, nature and financial values of the sanctions issued to noncompliant mining projects operating under the conditions of environmental licenses. First, through literature reviews, the study characterized the institutional and regulatory framework in which administrative sanctions are applied. Content analyzes of 29 infraction processes further revealed that lump sum fines are the preferred option of administrative sanction in EIA follow-ups. The analysis also revealed that the fines could be perceived as disproportionally small if one considers the size and financial power of non-compliant companies. The great majority of the fines were paid by developers: a fact that contradicts previous empirical findings and anecdotal evidence in Brazil. Overall, the study suggests that the impact of administrative sanctions in corporate behavior, while unclear, is likely small. The study concludes by discussing practical and academic implications. Highlights: The implementation of administrative sanctions in EIA follow-ups is explored. Empirical findings related to mining projects are collected in southeastern Brazil. Fines are the preferred administrative sanction. Arguably, values of fines are disproportionally small. Administrative sanctions are potentially weak in affecting corporate behavior.